2017
DOI: 10.1371/journal.pntd.0005713
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and parasitological factors in parasite persistence after treatment and clinical cure of cutaneous leishmaniasis

Abstract: BackgroundThe determinants of parasite persistence or elimination after treatment and clinical resolution of cutaneous leishmaniasis (CL) are unknown. We investigated clinical and parasitological parameters associated with the presence and viability of Leishmania after treatment and resolution of CL caused by L. Viannia.MethodsSeventy patients who were treated with meglumine antimoniate (n = 38) or miltefosine (n = 32) and cured, were included in this study. Leishmania persistence and viability were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
0
32
2
1
Order By: Relevance
“…Of course, a positive ELISA index does not necessarily reflect a recent Leishmania infection. Anti-Leishmania antibodies and possibly also the parasites themselves, are known to persist for very long (occasionally life-long), even in asymptomatic infections [9][10][11]; however, in the current study, relatively high ELISA indices were observed. Moreover, the seroprevalence in soldiers returning from their first mission tripled the prevalence found in a large group of Austrian soldiers tested prior to missions [12].…”
Section: Results and Conclusioncontrasting
confidence: 83%
“…Of course, a positive ELISA index does not necessarily reflect a recent Leishmania infection. Anti-Leishmania antibodies and possibly also the parasites themselves, are known to persist for very long (occasionally life-long), even in asymptomatic infections [9][10][11]; however, in the current study, relatively high ELISA indices were observed. Moreover, the seroprevalence in soldiers returning from their first mission tripled the prevalence found in a large group of Austrian soldiers tested prior to missions [12].…”
Section: Results and Conclusioncontrasting
confidence: 83%
“…Interestingly, recent reports from Colombia demonstrated a higher occurrence of Leishmania DNA in mucosal swab samples (45%e61.5%) from individuals with acute CL with apparently unaffected mucosa [8,9]. We speculate that this difference may be due to the mucosal tropism of the Leishmania (V.) subspecies circulating in Colombia since Leishmania panamensis causes concomitant cutaneous and mucosal lesions more frequently than other subspecies [10].…”
Section: Discussionmentioning
confidence: 71%
“…Because of the persistence of Leishmania infection following treatment and difficulties to isolate the parasite after treatment, the definition of therapeutic outcome is based solely on clinical findings, as explained by Olliaro et al 14,15 In case of a nonhealing lesion at the end of follow-up (persistent inflammatory signs or incomplete epithelialization), efforts should be made to isolate the parasite strain; however, the clinical outcome is independent of the persistence of infection. 14,16 If, at the end of follow-up, the lesion remains unhealed and no alternative diagnosis is considered, the recommendation is to give a new course of therapy. 17 Therefore, clinical expertise is crucial to define the outcome of treatment and to consider possible alternative diagnosis.…”
Section: Discussionmentioning
confidence: 99%